2011
DOI: 10.1016/j.ijdevneu.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic, transcriptional and posttranscriptional regulation of the tyrosine hydroxylase gene

Abstract: The activity of tyrosine hydroxylase (TH, EC 1.14.16.2) gene and protein determines the catecholamine level, which, in turn, is crucial for the organism homeostasis. The TH gene expression is regulated by near all possible regulatory mechanisms on epigenetic, transcriptional and posttranscriptional levels. Ongoing molecular characteristic of the TH gene reveals some of the cis and trans elements necessary for its proper expression but most of them especially these responsible for tissue specific expression rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
14

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 170 publications
(285 reference statements)
0
51
0
14
Order By: Relevance
“…Newly synthesized β-actin can polymerize more efficiently than "older" actin because of chaperone binding and protection from glutathionylation, a post-translational modification that decreases the rate of polymerization. Being the rate-limiting factor in the synthesis of catecholamines, TH expression and activity is highly regulated by both transcriptional and post-translational mechanisms (for review, see Lenartowski and Goc 2011). It would be interesting to compare the pattern of post-translational modification between newly synthesized and "older" TH.…”
Section: Discussionmentioning
confidence: 99%
“…Newly synthesized β-actin can polymerize more efficiently than "older" actin because of chaperone binding and protection from glutathionylation, a post-translational modification that decreases the rate of polymerization. Being the rate-limiting factor in the synthesis of catecholamines, TH expression and activity is highly regulated by both transcriptional and post-translational mechanisms (for review, see Lenartowski and Goc 2011). It would be interesting to compare the pattern of post-translational modification between newly synthesized and "older" TH.…”
Section: Discussionmentioning
confidence: 99%
“…This activation is mediated by indirect reflex excitation of the splanchnic nerve, which evokes large increases in catecholamine secretion (resulting in up to 70% of epinephrine content depletion) (47) accompanied by activation of TH enzyme and compensatory catecholamine biosynthesis in the adrenal medulla to maintain cellular catecholamine levels constant (41). As an index of catecholamine biosynthesis, we quantified changes in adrenal TH mRNA (25). After the hypoglycemic clamp, TH mRNA levels increased in all treatment groups compared with nonmanipulated controls.…”
Section: Transsynaptic Modulationmentioning
confidence: 99%
“…The explanation of the mechanism of TH gene regulation is one of the key issues in the field of neurology. Only a few laboratories have studied epigenetic mechanisms of the TH gene expression during the last decade [13,30]. We demonstrated that H3 acetylation showed a significant increase 24 h after chronic morphine treatment in the LC.…”
Section: Quantification Of Morphine-induced Histone Modifications At mentioning
confidence: 87%
“…These experiments make it evident that histone H3 acetylation may be involved in the molecular basis of neural and behavioral responses to addictive drugs [18,29]. In addition to histone modifications, other epigenetic systems including DNA methylation and microRNAs have also shown to affect the activity of the TH gene in a variety of animal models [30]. Thus, it is well established that TH gene methylation causes a decrease in TH expression, for example, in mesocortical projection of dopaminergic neurons after a mild isolation stress in a mouse model of depression [31].…”
Section: Introductionmentioning
confidence: 98%